Formulasi tablet hisap ekstrak etanol daun kemangi (Ocimum sanctum L.) dengan variasi konsentrasi bahan pengikat gelatin - Putri Nuryana; Windah Anugrah Subaidah; Agriana Rosmalina Hidayati (Sasambo Journal of Pharmacy, 2023)
Basil leaves (Ocimum sanctum L.) contain secondary metabolites as inhibitors of the growth of pathogenic microbes in the mouth, so they can be used as lozenges. The choice of binder in the formulation is very important, because it can affect the physical properties of the tablet. The purpose of this study was to determine the content of secondary metabolites in basil leaf extract and determine the best formula for lozenges of ethanol extract of basil leaves based on variations in gelatin binding agents. Basil leaves were extracted using the sonication method with 96% ethanol solvent and subjected to phytochemical screening (test tube and TLC). Tablets were formulated using the wet granulation method with variations of gelatin in formula 1 (5%), formula 2 (7.5%), and formula 3 (10%). The physical properties of the granules are evaluated and compressed. The resulting tablets were evaluated for physical properties. The results showed that basil leaves contained compounds belonging to the class of flavonoids, saponins and tannins. The results of the granule flow time test for formula 1 and 2 did not meet the requirements, formula 3 met the requirements for the Indonesian Pharmacopoeia Edition III. The angle of repose, settling, and granule water content tests (formula 1, 2, and 3) met the requirements of the Indonesian Pharmacopoeia Edition III. The results of tablet evaluation in the weight uniformity test for formulas 1, 2, and 3 were 257 mg ± 0.226; 248 mg ± 0.068 and 253 mg ± 0.157. Tablet hardness test of 3.721 kg ± 0.268; 4.221 kg ± 0.929 and 6.636 kg ± 1.035. Tablet friability test of 3.4% ± 0.152; 1.1% ± 0.264 and 0.9% ± 0.1. The disintegration time test was 7.6 minutes ± 2.452; 11 minutes ± 2.154 and 18.6 minutes ± 4.016. From this study it can be concluded that the ethanol extract of basil leaves has secondary metabolites of flavonoids, saponins and tannins. Variations in gelatin binder affect the physical properties of the tablet, where the concentration of gelatin binder is best in formula 3 (10%).